Deconstructing Income and Income Inequality Measures: A Crosswalk from Market Income to Comprehensive Income - Armour, Philip; Burkhauser, Richard V; Larrimore, Jeff (American Economic Review, 2013)
Recent research on levels and trends in the United States in income inequality vary substantially in how they measure income. We show the sensitivity of alternative income measures in capturing income trends using a unified data set. Focusing solely on market income or including realized taxable capital gains based on IRS tax return data in more comprehensive household income measures will dramatically increase inequality growth compared to capital gains measures more in keeping with Haig-Simons principles. Using a measure of yearly accrued capital gains dramatically reduces observed growth in income inequality across the distribution, but also equalizes income growth since 1989.